White Ginger (Zingiber Officinale) Decoction as a Complementary Therapy to Reduce Blood Pressure in Elderly Patients with Hypertension - Suprayitno, Guruh; Patawaran, Dini; Kurniawan, Nagita Bertha; Septyan, Nabila Aulya; Pakarang, Ferdi Bunga; Kok Mesa, Nofita Dewi (Jurnal Keperawatan Florence Nightingale, 2025)
Background Antihypertensive drugs in the elderly often cause side effects so that complementary therapy is needed, such as the use of herbal products. One effective herbal product is ginger because it contains the chemical compounds gingerol and shogaol which can function to lower blood pressure. The aim is to determine the difference in systolic and diastolic blood pressure between before and after treatment. This research method uses a quasi-experimental approach with a One Group Pretest-Posttest Design. The sample consisted of 35 elderly people with hypertension who were selected by purposive sampling. The intervention was in the form of giving 4 grams of white ginger decoction boiled in 200 ml of water. Researchers gave the white ginger decoction 2 times a day (morning and evening) for 7 days. The instrument used was a daily blood pressure observation sheet. Data analysis used a paired t-test with a significance level of p <0.05. Research results The average systolic blood pressure of respondents decreased from 150.37 mmHg to 133.34 mmHg, while diastolic blood pressure decreased from 90.20 mmHg to 69.74 mmHg. The statistical test results showed a significant difference between the pre-test and post-test scores, with a p-value of 0.000 (p < 0.05). Conclusion: White ginger decoction has been shown to be effective in lowering blood pressure in hypertensive elderly patients. Nursing practice recommends integrating this intervention into education and support programs for the elderly, along with regular monitoring to ensure its safety and effectiveness.